(untitled) (Ustozlar uchun, 2026)
This paper explores the effectiveness of interactive vocabulary instruction in enhancing learners’ communicative competence in English language classrooms. The research is grounded in Communicative Language Teaching, Task-Based Learning, Cognitive Load Theory, and Dual Coding theory. Within the context of Uzbekistan’s educational reforms, developing communicative competence has become a national priority, which requires innovative, learner-centered approaches to vocabulary teaching. A classroom- based action research methodology was applied, involving a series of interactive vocabulary activities such as “ Where are you from?”, “Colorful Plane ”, “ Smart ball”, “Magic snowball” and “ Happy fish”.